Portofolio Optimal Investasi Saham dari 6 Sektor pada Indeks LQ45 Periode 2015-2018: Optimal Portfolio Stock Investment from 8 Sectors of LQ45 During Period 2015-2018 - Benyamin Verkino; Bonar M. Sinaga; Trias Andati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
The purpose of this research is to build an optimum investment portfolio of stocks using Single Index Model (SIM) from 31 stocks of 8 sectors LQ45 indices (trade, mining, infrastructure, consumer, industry, agriculture, finance, and properti) during period 2015-2018. Based on the result of research, investor can form an investment portfolio that consists of 4 stocks (BBCA, SRIL, PTBA, and WSKT from finance, industry, mining, and property sectors) with portfolio’s expected rate of return of 0.351% per week and portfolio’s variance of 0.039% per week, compared with IHSG’s rate of return and variance for 0.091% and 0.037% per week. Signifcance’s test using one sample t-test shows portfolio’s return is significantly greater compared with market’s return or IHSG. Performance measurement of portfolio by using Sharpe, Treynor, and Jensen’s ratio shows a positive ratio compared to IHSG (Sharpe 0.117, Treynor 0.002, Jensen: 0,002) which means this portfolio will give higher rate of return than what is being offered by IHSG. Keywords: IHSG, LQ45, portfolio, sector, single index model